Eating from a salad bowl: Examining the cognitive demands and levels of difficulty in the Setswana NSC examination question papers - Sebate, PM (South African Journal of African Languages, 2017)
The aim of this article is to address the apparent lack of confidence in the quality assurance processes in the teaching and assessment of African languages, including Setswana. The article looks at whether the Setswana Grade 12 question papers accommodate and maintain a balance between the lower, middle and higher order cognitive demands and levels of difficulty. The importance of assessing cognitive demands, levels of difficulty and principles of high-quality assessment practices in the Setswana question papers, in relation to subject content knowledge, as processes to assure quality, cannot be overemphasised. One hundred and twenty-six Grade 12 Setswana examination question papers were analysed. The analysis was underpinned by Vygotsky's theory of constructivism for assessment as it puts more emphasis on the learner as an active 'maker of meaning' of the content that is taught. A desktop approach was used, and the examination question papers were analysed through Bloom's taxonomy as a framework or a key tool used in standardised assessment. The results of the research done prove that, although there are challenges in terms of resources, whether human or material, the Setswana Grade 12 examination question papers are of an appropriate standard and are fit for the purpose they are designed for.